2021
DOI: 10.1111/sed.12891
|View full text |Cite
|
Sign up to set email alerts
|

A giant lacustrine flood‐related turbidite system in the Triassic Ordos Basin, China: Sedimentary processes and depositional architecture

Abstract: Turbidites have been regarded as an important sedimentary infilling component in both oceans and lakes, but limited studies have been performed on the mechanisms governing the initiation and development of lacustrine turbidite systems. The present study offers unique insight into the controls and potential extent of ancient lacustrine turbidite systems by an investigation of the Triassic Ordos Lake, where a large turbidite system had been traced across >25 653 km 2 . This article shows by comparison that the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 74 publications
(175 reference statements)
0
8
0
Order By: Relevance
“…Hyperpycnites in depression basins have been widely reported, such as that in the Ordos Basin (Chen et al, 2021; Xian et al, 2018; Yang et al, 2017), and the Songliao Basin (Dou et al, 2021; Pan et al, 2017) in China. This study demonstrated that there are many differences between hyperpycnites in rift basins and depression basins (Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperpycnites in depression basins have been widely reported, such as that in the Ordos Basin (Chen et al, 2021; Xian et al, 2018; Yang et al, 2017), and the Songliao Basin (Dou et al, 2021; Pan et al, 2017) in China. This study demonstrated that there are many differences between hyperpycnites in rift basins and depression basins (Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that there are many differences between hyperpycnites in rift basins and depression basins (Yang et al, 2020). Hyperpycnites in depression basins are usually dominated by fine‐grained sandstone, with distinct channel‐lobe system and long transport distance more than 100 km (Chen et al, 2021; Dou et al, 2021; Pan et al, 2017; Xian et al, 2018; Yang et al, 2017). However, hyperpycnites in rift basins are characterized by a wide range of grain size range from gravel to fine‐grained sands (Figure 3) (Liu et al, 2021; Yang et al, 2019, 2020; Yuan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, hyperpycnal flow deposits (‘hyperpycnites’) are commonly described from various lacustrine and glacio‐deltaic successions, reflecting the favourable conditions for dense underflows to form in these environments (e.g. Nemec et al ., 1999; Zavala et al ., 2006; Girard et al ., 2012; Yang et al ., 2017; Cao et al ., 2018; Bellwald et al ., 2020; Chen et al ., 2021). Despite recent developments in the surveillance of naturally occurring turbidity currents (Clare et al ., 2016; Azpiroz‐Zabala et al ., 2017; Hage et al ., 2019; Maier et al ., 2019; Heijnen et al ., 2020; Heerema et al ., 2022; Pope et al ., 2022; Talling et al ., 2022), monitoring data of hyperpycnal flows in the marine realm is relatively sparse.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a growing body of literature describing hyperpycnites in ancient and modern submarine lobes, suggesting that hyperpycnal flows may transfer sand into deep‐water environments (e.g. Mutti et al ., 2003; Bourget et al ., 2010; Zavala et al ., 2012; Warrick et al ., 2013; Chen et al ., 2021). This is enigmatic, because it has been shown that hyperpycnal flows entering marine basins typically deposit their sandy load near the river mouth (e.g.…”
Section: Introductionmentioning
confidence: 99%